Satisfaction on Nursing Management of Postoperative Complications Rendered by Surgical Staff Nurses in Philippines - Modesto P. Fucio; Alma Lanzon Fucio; Cyril B. Romero (The Indonesian Institute of Science and Technology Research, 2023)
This study examined the satisfaction levels of surgical staff nurses and clients on the nursing management of postoperative complications in different hospitals in Iriga City, Philippines. The study investigated the personal and professional attributes of surgical staff nurses, the level of satisfaction of nursing care in preventing postoperative complications, the relationship between personal and professional attributes and interventions, and proposed measures based on the study's findings. The results showed that most surgical staff nurses were female, had a baccalaureate degree, attended training in the surgical area, and had 6 to 10 years of experience. Both staff nurses and patients were satisfied with the nursing management rendered in preventing postoperative complications, and there was no significant difference in satisfaction levels between clients and staff nurses. There was no significant relationship between the profile of staff nurses and the level of satisfaction with nursing care for preventing postoperative complications.